Effect of 2-dodecyl-6-methoxycyclohexa-2, 5-diene-1, 4-dione, isolated from Averrhoa carambola L. (Oxalidaceae) roots, on advanced glycation end-product-mediated renal injury in type 2 diabetic KKAy mice. (15th March 2021) - Ni, Zheng; Lin, Xing; Wen, Qingwei; Kintoko,; Zhang, Shijun; Huang, Jianchun; Xu, Xiaohui; Huang, Renbin
Abstract: The roots of Averrhoa carambola L. (Oxalidaceae) have a long history of medical use in traditional Chinese medicine for treating diabetes and diabetic nephropathy. 2-dodecyl-6-methoxycyclohexa-2, 5-diene-1, 4-dione (DMDD) was isolated from the tuberous roots of Averrhoa carambola L. The purpose of this study was to investigate the beneficial effect of DMDD on the advanced glycation end-product-mediated renal injury in type 2 diabetic KKAy mice with regard to prove its efficacy by local traditional practitioners in the treatment of kidney frailties in diabetics. KKAy mice were orally administrated DMDD (12.5, 25, 50 mg/kg body weight/d) or aminoguanidine (200 mg/kg body weight/d) for 8 weeks. Hyperglycemia, renal AGE formation, and the expression of related proteins, such as the AGE receptor, nuclear factor-κB, transforming growth factor-β1, and N ε -(carboxymethyl)lysine, were markedly decreased by DMDD. Diabetes-dependent alterations in proteinuria, serum creatinine, creatinine clearance, and serum urea-N and glomerular mesangial matrix expansion were attenuated after treatment with DMDD for 8 weeks. The activities of superoxide dismutase and glutathione peroxidase, which are reduced in the kidneys of KKAy mice, were enhanced by DMDD. These findings suggest that DMDD may inhibit the progression of diabetic nephropathy and may be a therapeutic agent for regulating several pharmacological targets to treat or prevent of diabetic nephropathy.